Internalização dos conceitos da ISO 14.001 em Cooperativa de Catadores. o caso da cooperativa de Rio Claro/SP - Lima, Valdemir dos Santos de (Universidade Federal de São Carlos, 2018)
The strong production of solid waste in contemporary urban society has demonstrated the importance and necessity of establishing strategies aimed at the management and management of these wastes in Brazilian cities, especially the promotion of sustainable practices in the social, economic and environmental spheres. The promotion of selective collection programs is one of the most important strategies to minimize the negative environmental impacts of solid waste generation. In this sense, one of the actions developed by the municipality of Rio Claro/SP was the institution of COOPERVIVA - Work Cooperative of Waste Pickers of Rio Claro/SP. The objective of this cooperative is to: collect, triage store and market the recyclable materials coming from the selective collection made. The present research made it possible to verify the activities developed by the enterprise in three aspects: a) social inclusion, through the insertion of waste pickers from the former controlled landfill; b) the generation of work and income, through the commercialization of recyclable materials; c) increase the useful life of the Landfill and the correct disposal of recyclable materials. However, the managerial processes of such organizations demonstrate weaknesses in daily practices, as well as issues related to the organization's environmental management. Thus, considering these aspects, the study involved the implementation of ISO 14.001 precepts in cooperatives or associations of collectors, with COOPERVIVA as its main object. The research aimed at improving the physical and structural conditions of the organization, especially of the individuals belonging to the cooperative, in order to improve the work done by the collectors and to mitigate possible environmental impacts, guided by the National Solid Waste Policy (Law 12,305 / 2010).
Internalization of the concepts of ISO 14.001 in Cooperadores de Catadores. the case of the cooperative of Rio Claro/SP
Keywords: Gestão de resíduos sólidos; Cooperativa de catadores; Sistema de gestão ambiental; Coleta seletiva; Política Nacional de Resíduos Sólidos; Solid waste management; Collectors cooperative; Environmental management system; Selective collect; National Policy on Solid Waste; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS